2019
DOI: 10.1101/566513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic profiling of the oncogenic septin 9 reveals isoform-specific interactions in breast cancer cells

Abstract: Septins are a family of multimeric GTP-binding proteins, which are abnormally expressed in cancer. Septin 9 (SEPT9) is an essential and ubiquitously expressed septin with multiple isoforms, which have differential expression patterns and effects in breast cancer cells. It is unknown, however, if SEPT9 isoforms associate with different molecular networks and functions. Here, we performed a proteomic screen in MCF-7 breast cancer cells to identify the interactome of GFP-SEPT9 isoforms 1, 4 and 5, which vary sign… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 117 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…Recent studies revealed that SEPT6 was the upstream gene of UBC in prostate cancer and inhibited tumor growth by regulating UBC [33]. Other evidences showed that SEPT6 was also participated in the pathogenesis of breast cancer and hepatocellular carcinoma, which suggested that targeting SEPT6 may be a new therapeutic strategy for cancers [34,35]. Overexpression of SEPT7 plays a crux role in inhibiting the growth and migration of glioma cells [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that SEPT6 was the upstream gene of UBC in prostate cancer and inhibited tumor growth by regulating UBC [33]. Other evidences showed that SEPT6 was also participated in the pathogenesis of breast cancer and hepatocellular carcinoma, which suggested that targeting SEPT6 may be a new therapeutic strategy for cancers [34,35]. Overexpression of SEPT7 plays a crux role in inhibiting the growth and migration of glioma cells [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, previous studies showed that enabled homolog (ENAH), an actin regulatory protein of the enabled/vasodilator-stimulated phosphoprotein family, promoted the proliferation, invasion and epithelial-mesenchymal transition of breast cancer cells when overexpressed (12,13). Also, other studies showed that septin 9 (SEPT9), an oncogenic protein, was dysregulated in patients with breast cancer with lymph node metastases and regulated the migration of breast cancer cells via ras homolog family member A/focal adhesion kinase signaling (14,15). Additionally, epidermal growth factor (EGF) has been reported to interact with its receptor to regulate the carcinogenesis and malignant behavior of breast cancer cells (16,17).…”
Section: Potential Of Blood Exosomal Enah Sept9 Egf Mmp-9mentioning
confidence: 99%
“…Because centrosomal levels of SEPT7 decrease during mitosis, and SEPT7 depletion impacts on entry into S phase [57], SEPT7 appears to function in centrosome duplication before mitosis. Although the precise role of SEPT7 is unknown, p150 GLUED localizes to the subdistal appendages of the mother centriole which anchor microtubule minusends, and impacts on the recruitment of the subdistal appendage proteins ninein and CEP170 which interact with SEPT9 and SEPT1, respectively [79][80][81]. Of note, SEPT1 is also enriched in spindle poles [82].…”
Section: Septins Regulate the Localization And Functions Of Mitotic Microtubule Motorsmentioning
confidence: 99%